Factors Influence Entrepreneurial Intention - Andika Chandra Prasetyo; Sudibyo, Toto; Miftah, Moh; Nurkhayati, Nurkhayati (Moneter: Jurnal Keuangan dan Perbankan, 2024)
The employment rate in Indonesia in August 2022 reached 5.86%. One of the solutions to overcome unemployment is entrepreneurship. Based on Perpres Nomor 115 Tahun 2021, national priorities one and three in the 2020 RKP are “Pembangunan Manusia dan Pengentasan Kemiskinan” and “Nilai Tambah Sektor Riil, Industrialisasi dan Kesempatan Kerja”. To strengthen economic resilience to achieve quality and equitable growth, two indicators are used, namely an increase in the national entrepreneurship ratio 3.9% and the growth of new entrepreneurs of 4% by 2024. In 2022, Indonesia’s entrepreneurship ratio was still around 3.47%. The low ratio of entrepreneurship raises the question, of what factors influence a person’s entrepreneurial intention so that there is a desire for entrepreneurship in the workforce in Indonesia.